BIOLOGY OF THE LARGE-SCALED TONGUE SOLE CYNOGLOSSUS MACROLEPIDOTUS (BLEEKER)
The biometry of C. macrolepidotus us&ng the regression equ tion y = a + bx has lnen stllidi1ed; the regression Hnes based on the angle of <the tangent show that total length ha’s the fastest growth and ,the eye d:,a:me,ter the slowest ’the food of c. macrolepidotus com jsts of crust’a’ceans, bivallves, po!